Diseño de sistema de iluminación orientado al uso racional y eficiente de la energía en las aulas del piso 3, 4 y auditorio del bloque 2, sede sur en Bogotá D.C. de la universidad Antonio Nariño (2025)
The study arises from the need to optimize the lighting system in the classrooms on the 3rd and 4th floors and the auditorium of Block 2, South Campus in Bogotá D.C. of the Antonio Nariño University, given that it does not meet the lighting levels required by the Technical Regulations for Lighting and Public Lighting (RETILAP).